Kekuatan Eksekutorial Putusan Badan Pengawas Pemilu dalam Penyelesaian Pelanggaran Administrasi Pemilihan Umum - Usman Usman; Az Zahra Zain Auralia; Hanni Ambarasti (Jurnal Mengkaji Indonesia, 2022)
Abstract: The Election Supervisory Body (Bawaslu) is an election management body that oversees the implementation of elections under the provisions of law to receive, examine, review, and rule on violations of the election administration. The decision issued by Bawaslu and its apparatus is intended so that the decision can be directly implemented (self-executing) and is mandatory, therefore, it might arises questions supposing the General Elections Commission (KPU) did not implement the decision made by Bawaslu. Apart from that, another question arises about the executorial power of the Bawaslu in resolving the matter of the election administrative violations. Purpose: The method used in this research is normative legal research. There are several approaches in legal research, however, using this approach will have the author able to obtain information from various aspects in seeking the answer to the issues. The approach in this research is a statute approach. Design/Methodology/Approach: The method used in this research is normative legal research. There are several approaches in legal research, however, using this approach will have the author able to obtain information from various aspects in seeking the answer to the issues. The approach in this research is a statute approach. Findings: As stated in the provisions of the General Election Law, “KPU, Provincial KPU, and Regency/Municipal KPU are “obliged” to implement the decision of Bawaslu, Provincial Bawaslu, and Regency/Municipal Bawasul no later than 3 (three) working days from the date the decision is read.” If the decision is not implemented, “In the event that the KPU, Provincial KPU, Regency/Municipal KPU, PPK, PPS, or the Contestants do not implement the decisions of Bawaslu, Provincial Bawaslu, Regency/Municipal Bawaslu, therefore Bawaslu, Provincial Bawaslu, Regency/Municipal Bawaslu file a complaint to DKPP.” Originality/Value: There have not many studies of the executorial power of the Bawaslu decision, therefore the author considers this as original research.